2018
DOI: 10.1002/ctpp.201800017
|View full text |Cite
|
Sign up to set email alerts
|

Breather structures in a plasma with warm ions and Cairns electrons

Abstract: The modulational instability (MI) of ion-acoustic waves (IAWs) in a two-component non-Maxwellian hot plasma with Cairns distributed electrons is investigated. Using the derivative expansion method, a non-linear Schrödinger equation (NLSE) is obtained. The criterion for MI, which occurs for small values of the carrier wavenumber, is obtained. It is found that non-thermal parameter modifies the criteria for MI instability. The analytical solutions of NLSE in the form of various types of freak waves, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(113 reference statements)
0
0
0
Order By: Relevance
“…They observed that an increase in temperature of degenerate trapped species leads to an increase in the area of MI of IA waves and decrease in amplitude of breather structures. MI of IA waves in Cairns distributed hot ion plasma was reported by Shan et al [10] to explore the breather structures and it was reported that nonthermality significantly modifies the region of MI and amplitude of nonlinear structures. Employing the Gardner equation, a broad spectrum of nonlinear IA wave structures and their group dynamics are examined in a negative ion plasma by Ghosh [12].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…They observed that an increase in temperature of degenerate trapped species leads to an increase in the area of MI of IA waves and decrease in amplitude of breather structures. MI of IA waves in Cairns distributed hot ion plasma was reported by Shan et al [10] to explore the breather structures and it was reported that nonthermality significantly modifies the region of MI and amplitude of nonlinear structures. Employing the Gardner equation, a broad spectrum of nonlinear IA wave structures and their group dynamics are examined in a negative ion plasma by Ghosh [12].…”
Section: Introductionmentioning
confidence: 95%
“…A series of equations may be obtained by replacing Equations ( 9) and (10) in Equations ( 2)-( 7) and equating the coefficients of different powers on each side. The following KP equation has been obtained from the above equations [2,5] :…”
Section: The Kp Equation and Derivation Of Nonlinear Schr öDinger Equ...mentioning
confidence: 99%
See 1 more Smart Citation